The somme - Prior, Robin; Wilson, Trevor 1928- (Yale University Press, 2016)
"Despite superior air and artillery power, British soldiers died in catastrophic numbers at the Battle of Somme in 1916. What went wrong, and who was responsible? This book meticulously reconstructs the battle, assigns responsibility to military and political leaders, and changes forever the way we understand this encounter and the history of the Western Front"--Publisher description